2002
DOI: 10.1073/pnas.022493799
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of Clostridium perfringens , an anaerobic flesh-eater

Abstract: Clostridium perfringens is a Gram-positive anaerobic spore-forming bacterium that causes life-threatening gas gangrene and mild enterotoxaemia in humans, although it colonizes as normal intestinal flora of humans and animals. The organism is known to produce a variety of toxins and enzymes that are responsible for the severe myonecrotic lesions. Here we report the complete 3,031,430-bp sequence of C. perfringens strain 13 that comprises 2,660 protein coding regions and 10 rRNA genes, showing pronounced low ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
582
1
16

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 668 publications
(612 citation statements)
references
References 50 publications
13
582
1
16
Order By: Relevance
“…An alignment of the various VirR boxes showed that the sequences of these boxes were similar, but not identical (38) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An alignment of the various VirR boxes showed that the sequences of these boxes were similar, but not identical (38) (Fig. 3A).…”
Section: Resultsmentioning
confidence: 99%
“…When other VirR boxes that have been detected in the C. perfringens genome (38) were inserted upstream of pfoA, in lieu of the pfoA VirR boxes, we found that they conferred different levels of perfringolysin O activity in the reporter system. The results suggested that differences in the in vitro binding abilities were not a likely cause of the different levels of transcriptional activation that were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(46) The Bacteria classes Actinobacteria and Clostridia were enriched in the inhibited reactors as well; both of these classes contain pathogenic bacterial strains which may have antibiotic resistance, and the Actinobacteria class contains many acid tolerant bacteria. (47,48) …”
Section: The Impact Of Tcc On Microbial Community Structure Of Anaeromentioning
confidence: 99%
“…Another feature that could contribute to the efficiency of pHS30 may relate to the use of the resistance determinant catP, isolated originally from a strain of C. perfringens (1). C. perfringens and F. nucleatum are characterized by strikingly low genomic GC content, at 29 and 27%, respectively (22,35). Differences in the promoters or codon bias may affect expression of the catP gene versus the erm determinants (32), thereby influencing the recovery of transformants.…”
Section: Discussionmentioning
confidence: 99%